A Student and Early Career Professional Perspective of Human Factors Career Options. (September 2013) - Neilson, Brittany; Proaps, Alex; Smith, Dustin; Tharanathan, Anand; Werner, Nicole
The goal of this panel is to facilitate a discussion among current students and recent graduates about their decision-making process in choosing one of the three main sectors in human factors as a career: academia, government, and industry. Panelists will present their relevant academic and applied experiences and describe how theses experiences shaped their career path. Major themes of the panel will include a student perspective on the increasing interest in industry as opposed to academia among individuals pursuing a career in human factors and how this may affect future education and training of human factors professionals.